Identifikasi Penyebab Penyakit Layu pada Tanaman Stroberi (Fragaria sp.) di Desa Pancasari dan Potensi Pengendaliannya dengan Mikroba Antagonis - SARI, I GUSTI AYU DEVI VALENIA; WIRYA, GUSTI NGURAH ALIT SUSANTA; SUDIARTA, I PUTU (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Identification of the causes of lute diseases in strawberry plants (Fragaria sp.) In Pancasari Village And Control Potential By Microbial Antagonists Strawberries (Fragaria sp.) Is one of the most popular fruits of the community because it has many benefits. Strawberry development in Bali is mostly done in the Bedugul area including Pancasari Village because it has a suitable climate for the development of strawberry plants. This study aims to identify the wilting disease that causes a decline in the yield of strawberry plants that reach 95% in Pancasari Village, Sukasada District, Buleleng Regency. The use of synthetic chemical pesticides is the only way that farmers do in Bedugul area to suppress the strawberry disease. Several studies have reported that unwise and excessive use of synthetic chemical pesticides can cause problems and disrupt environmental balance. Control of plant diseases using microbial antagonists is one of the alternative of environmentally friendly control The method used is isolation, identification, pathogenity test and inhibit microbe antagonistic inhibitory test by dual culture technique. Research activities included (1) sampling of symptomatic plants, (2) isolation and identification of associated fungi at root of strawberry plant, (3) isolate fungal pathogenic test (4) isolation of microbial antagonistic candidate, (5) In Vitro test of antagonistic microbial ability Controlling the pathogen of wilt disease in strawberry plants. The results showed that, mushrooms associated with rooting of strawberry plants were pathogens of the genus Verticillium sp. In Vitro antagonistic test with Verticillium sp. Showed the results in which microbial antagonists were able to suppress pathogen growth by 64%. Anatagonic microbes from the fungus Trichoderma sp. Able to suppress the growth of pathogens of wilt disease (Verticillium sp.). Trichoderma sp. Has the ability to grow quickly Trichoderma sp. Also produce various compounds or enzymes that serve to inhibit or break down the cell walls of plant pathogens.